(untitled) (CIPEEX, 2025)
Objective: This study aimed to evaluate the adherence of health professionals to bundle-based guidelines in Intensive Care Units (ICUs). Methods: It was a cross-sectional, exploratory, and descriptive study conducted between September and December 2023 in ICUs of hospitals in Anápolis – GO, with a sample of health professionals selected by simple random probabilistic sampling. Data collection was carried out through semi-structured interviews and questionnaires addressing sociodemographic aspects and practices related to bundles, with descriptive statistics and frequency analysis applied. Results: The results showed that most participants were from the private hospital (64.86%) and worked the night shift (54.17%), with the predominant age group being 25 to 35 years (58.33%) and most being female (94.30%). The majority of professionals knew the elements of the bundles (78.38%) and had participated in training on the subject (70.27%), although with variations in frequency. Adherence to recommended practices such as protective barriers and hand hygiene was high, and perceptions regarding the effectiveness of communication and the importance of bundles for care were positive, with most professionals feeling confident in implementation. Conclusion: It is concluded that adherence to bundle-based practices is significant in the ICUs studied, with good knowledge and training among professionals, although there are areas for improvement, especially in the regularity of training and in the culture of incident reporting, making continuing education and the promotion of a safety culture essential to enhance the prevention of healthcare-associated infections.